Effect of Cation Size on Electrochemical Properties of Polymer Electrolyte - Jawad, Mohammed kadhim (Iraqi Journal of Physics, 2019)
Polymer electrolytes systems compose of (PEO+KI+I2) and (PEO+RbI+I2) with different concentration, and a fixed amount of ethylene carbonate (EC) and propylene carbonate (PC) over temperatures range 293-343 K prepared by solution cast method. The conductivity and dielectric constant of the gel electrolytes were studied. The conductivity of the electrolytes Ss & Hs increases steadily with increased concentration of salt KI and RbI. The higher value of conductivity of (4.7 10-3 @ RT S.cm-1) for S5 electrolyte which contains (KI 50%). Whereas the maximum amount of conductivity of (5.4 10³ @RT S.cm⁻ˡ) for H5 electrolyte which contains (RbI 50%) the ionic conductivity depends on the ionic radii of the migrating species (cation K⁺, Rb⁺) effect on it. As the temperature increase, the number of free ions also increases, thus increases the diffusion of ions through their free volume of the polymer. The dielectric constant decrease at higher frequencies due to the inability of dipoles to align quickly with the change of applied field. The dielectric constant proportional positively with variation temperature causes an increase in the dielectric constant. The higher the value of (εr), the better is the electrical conductivity.